DEVELOPMENT OF A NEW SPECTROPHOTOMETRIC METHOD FOR FULL CHARACTERIZATION OF TURBIDITY - Mutisya, Stephen (East Carolina University, 2022)
Characterization of turbid materials by determining their inherent optical properties have attracted strong research interest for potentially wide applications in fields such as material analysis and biomedical optics. The response of a homogeneous turbid sample to an optical excitation can be accurately described by absorption coefficient [mu]a, scattering coefficient [mu]s, and anisotropy factor g based on the radiative transfer theory. Existing spectrophotometric methods typically uses integrating spheres to acquire the light signals. These approaches, however, are difficult to be translated into instruments for users without special training. The research goal of this dissertation research project is two-fold: (1) Develop and validate a new spectrophotometric method without integrating sphere to characterize turbidity for optically thick samples by three optical parameters of [mu]a([lambda]), [mu]s([lambda]) and g([lambda]). (2) Demonstrate the applicability of the new spectrophotometric method as a label-free assay of cell suspension samples treated by a chemotherapy drug. An experimental system has been developed to measure signals of diffuse reflectance Rd, diffuse transmittance Td and forward transmittance Tf as functions of wavelength [lambda] between 460 and 1000nm from two types of samples. We have inversely determined the optical parameters of polystyrene microsphere samples by an in-house build individual photon Monte Carlo (iMC) simulation software. Validation of the new method has been achieved by comparing the optical parameters determined from the measured signals to those predicted by the Mie theory. In addition, we have applied the validated method to obtain the optical properties of MCF-7 cell samples treated by an apoptosis inducing drug doxorubicin for three different doses and three post-treatment times. By comparing to apoptosis measurement results of MTT assay and fluorescent flow cytometry, we were able to qualitatively demonstrate the potential applications of the new spectrophotometric method as a label-free assay to detect cellular apoptosis in treated samples.
Keywords: OPTICS; MCF7; Turbidity; Spectrophotometry; Mie scattering